Objetos mediadores em museus - Inês Ferreira (Midas: Museus e Estudos Interdisciplinares)
A participatory museum encourages visitors to approach their visit as a creative and personal experience. It enables each visitor to contribute with all of his or her experience, knowledge, and interests. Many exhibitions, however, do not promote this personal involvement. This paper presents a review of literature that suggests that mediation, particularly mediation objects, facilitate personal involvement, the construction of knowledge, and creativity. The theoretical problem is if more traditional museums can be open to participation and, in this context, our aim is to understand the role of mediation objects in this process. We discuss the use of mediation objects as a manner of adding multiple levels of relationship and ways of seeing, a potential that we consider as being underexploited in many museums. The article begins by presenting the museum as a participatory space that invites to an active and critical engagement - active, because the visitor is challenged to ‘do’ and not merely to ‘look’; critical because he/she is stimulated to think, choose, discuss and reflect. We then present different methods of using mediation objects to encourage visitors to engage with artefacts, using his/her memory, experience, knowledge and feelings. Biographical participation enhances the interaction between the inner world of the visitor and the artefacts and contents of the museum. This space in-between is the space of knowledge construction. Different ways of making a museum become a more creative and participatory place are presented, even if it is not an interactive museum, and the discussion may contribute to change practices, namely to rethink permanent exhibitions.